PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE THINK PAIR SHARE DI SEKOLAH DASAR - Richardo, David; S, Farida; Harni, Harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The researchis animed to improve the students’ learning outcomes in learning the Social Study Subject by using the Cooverative Learning, Think Pair Share Model at 5th grade of SDN 29 Pesisir Selatan.Types of this research was classroom action research with qualitative and quantitative approach. Subject of this research were teachers (practitioners) and 16 students. The result of research was improve a) Lesson plan the cycles of I was 82,1% and the cycles II of 92,8% b) Implementation teacher’s activity of I cycle was 76,5% and II cycle was 96,8% while implementation students activity of I cycle was 76,5% and II cycle was 96,8% c) the students learning outcomes in the I cycle was 73,4 and II cycle was 85,8. It can be concluded that used Cooperative Learning Model Type Think Pair Share can improve students achievement in learning social study of elementary school.Keyword : Learning outcomes, Social Study, Model